Simulation of emotional behaviours for virtual agents with personalities - Zhang, Yi (Curtin University, 2015)
We have proposed an improved emotion model based on the well-known PAD model in affective computing and the NEO PI-R personality model in psychology. A novel parameter Emotion Intensity (EI) is proposed to represent different strength of anger, disgust, fear, happiness and sadness. Another novel Resistant formulation is also proposed to effectively simulate the complicated negative emotions. Eight experiments are conducted to simulate different emotional responses under different stimuli with different personality traits.